Evaluating the Doctoral Program at the College of Education at King Khalid University in light of Quality Standards and Academic Accreditation from the Point of View of Faculty Members and Doctoral Students - Al-Ghahtany, Dhabia Garallah Fallah (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to evaluate the doctoral program at the College of Education at King Khalid University in the light of quality standards and academic accreditation from the point of view of faculty members and students. A stratified sample of (78); Of them, (33) faculty members, and (45) doctoral students. The research reached a number of results; The most important of which is that the degree of availability of quality standards and academic accreditation in the doctoral program at King Khalid University - from the point of view of faculty members and doctoral students - obtained an overall average of (2.89 out of 5), i.e. with a degree of availability (medium) and a percentage of (57.8%), and at the level of fields; It ranked in descending order: the first is the material capabilities, the learning resources with an average of (2.98), then the specifications of the educational program with an average of (2.92), then the management of the program with an average of (2.91) then community service with an average of (2.90) ensuring the quality of the program, and continuous improvement with an average of (2.88), then human potential with an average (2.86), then the educational regulations and systems with an average of (2.82), then teaching and learning with an average of (2.80), the last of which is the specifications of the educational program with an average of (2.79), all with a degree of availability (medium). Developing doctoral programs, developing admission system mechanisms, program management mechanisms, developing mechanisms to focus on faculty members, developing admission system mechanisms, The research recommended developing courses in doctoral programs to include practical aspects, developing the program’s absorptive capacity to provide opportunities for enrollment to the largest number of students, and working to spread awareness about the importance of applying quality standards and academic accreditation.